Digital Video Encryption Algorithms Based on Correlation-Preserving Permutations. (30th July 2007) - Socek, Daniel; Magliveras, Spyros; Ćulibrk, Dubravko; Marques, Oge; Kalva, Hari; Furht, Borko
Abstract : A novel encryption model for digital videos is presented. The model relies on the encryption-compression duality of certain types of permutations acting on video frames. In essence, the proposed encryption process preserves the spatial correlation and, as such, can be applied prior to the compression stage of a spatial-only video encoder. Several algorithmic modes of the proposed model targeted for different application requirements are presented and analyzed in terms of security and performance. Experimental results are generated for a number of standard benchmark sequences showing that the proposed method, in addition to providing confidentiality, preserves or improves the compression ratio.